Lidocaine-Loaded Hyaluronic Acid Adhesive Microneedle Patch for Oral Mucosal Topical Anesthesia - Tingting Zhu; Xixi Yu; Xin Yi; Xiaoli Guo; Longhao Li; Yuanping Hao; Wanchun Wang (MDPI AG, 2022)
The pain and fear caused by direct local injection of anesthetic or the poor experience with surface anesthetic cream increase the difficulty of clinical treatment for oral diseases. To address this problem, a hyaluronic acid microneedle patch (Li-HAMNs) that consists of fast-dissolving lidocaine hydrochloride (LDC)-loaded tips and a wet-adhesive backing layer made of polyvinyl alcohol (PVA)/carboxymethylcellulose sodium (CMC-Na) was fabricated to explore its potential use in dental topical anesthesia. Li-HAMNs could puncture the stratum corneum with an insertion depth of about 279 μm in the isolated porcine oral mucosal. The fast-dissolving tips could release LDC to improve the patients' convenience and compliance. Importantly, the backing layer, which has good adhesion ability and water-absorbing properties, could surmount the contraction and extension of oral masticatory muscles and the saliva scour. In the tail flick test, the topical anesthesia efficacy of the Li-HAMNs group was much better than clinical lidocaine cream (EMLA cream, LDC, 1.2 mg) in spite of a relatively lower LDC dose with Li-HAMNs (LDC, 0.5 mg). It is believed that the proposed adhesive microneedle patch could enhance transmucosal delivery of anesthetics and thus open a new chapter in the painless treatment of oral diseases.